Regulating Speech: A Comparative Analysis of Australia’s Racial Vilification Offence and Hong Kong’s National Security Law - Ka Hang Wong (Journal of Pragmatics Research, 2026)
This article undertakes a comparative critical historiographical analysis of Australia’s proposed 2026 racial vilification offence and Hong Kong’s National Security Law (NSL) to examine how legal regimes regulate speech through differing constructions of harm, threat, and legitimacy. Drawing on Flowerdew’s Critical Discourse Historiography (CDH), the study approaches law as a historically situated discourse that encodes assumptions about state power, social fragility, and political belonging. Through close textual analysis of statutory language and associated discourse, the article examines how the presence or absence of contextual exemptions shapes the legal boundaries of punishable expression, revealing a divergence in the presupposed ontology of power underpinning the two regimes. Although the proposed Australian offence was withdrawn, Australia’s hate speech framework operates within a liberal-democratic tradition that presupposes a strong state governing a pluralistic society, in which exemptions and contextual interpretation function as mechanisms for balancing harm mitigation against expressive freedom. By contrast, Hong Kong’s NSL presupposes a weak and vulnerable state, foregrounding sovereignty and security as overriding values and discursively constructing dissent as an existential threat. The absence of meaningful exemptions within the NSL facilitates a form of performative citizenship, in which loyalty is enforced through the policing of alternative political narratives. By situating both regimes within their historical and ideological trajectories, the article argues that exemptions are not peripheral technicalities but central discursive mechanisms that determine whether speech regulation functions as social governance or regime preservation, offering Hong Kong’s experience as a cautionary lens for debates on speech regulation in liberal democracies.